Implementation of the Land Management Application as an Effort to Prevent Land Disputes through Digitalization Services - Navasha Hadiya Putri; Yulia Hanoselina (Journal of Educational Management Research, 2025)
This study aims to evaluate the implementation of the Sentuh Tanahku application at the Land Office (ATR/BPN) in Padang City, focusing on its role in supporting the implementation of electronic certificates and preventing land disputes. A qualitative descriptive approach was employed, with data collected through in-depth interviews with office officials, staff, and service users, as well as document analysis. The analysis utilized the Miles, Huberman, and Saldana interactive model, incorporating triangulation techniques for data verification. The findings, based on the Technology Acceptance Model (TAM), indicate that the Sentuh Tanahku application significantly enhances land service effectiveness through features such as certificate checking, online queuing, and Swaplotting. The application’s user-friendly interface and adherence to ISO/IEC 27001 security standards were also highlighted. However, the study identified three main barriers: a preference for conventional services, concerns about data security, and disparities in digital literacy. These challenges hinder the complete adoption and impact of the application. This research has implications for educational management, particularly in promoting digital literacy programs. By addressing barriers such as security concerns and digital literacy gaps, academic institutions and government agencies can foster a more inclusive digital transition, ensuring that digital systems in public services are accessible and effective for all.